Infrastructure investment on the margins of the market: The role of niche infrastructure providers in the UK - Paolo Gerli; Jason Whalley (International Telecommunications Society (ITS), 2016)
Across Europe, policymakers and market forces are striving to deploy next generation access (NGA) networks and ensure ubiquitous access to superfast broadband services. Due to scale economies and sunk costs, the roll-out of NGA is expected to be profitable only for large-scale providers and in densely populated areas. This has resulted in an uneven distribution of NGA networks, which is expected to be complemented by public intervention. Nonetheless, alternative providers, such as utilities and local communities, have significantly contributed to NGA diffusion in many countries. Over the past five years, several small-scale initiatives have emerged in the UK, bringing fibre networks to urban and rural areas previously overlooked by either commercial or subsidised deployments. A multiple case study is here employed to investigate the nature and the drivers of niche providers in the UK NGA market. The comparison emphasised similarities and differences across these initiatives, identifying a number of elements recurring in their strategies. This analysis sheds light on the contribution of niche providers to bridging the digital divide in the UK and is meant to provide a preliminary assessment of their sustainability and potential growth.
Keywords: 330; Alternative broadband providers; niche strategies; digital divide